Degradation of Eosin Y in Water by Corona Treatment with a Dielectric Barrier Discharge Plasma. Issue 10 (10th August 2020) - Abd El-Gelil, Gehad M.; Mansour, Moustapha S.; Ebrahiem, Ebrahiem Esmail; EL-Shazly, Ahmed H.; Abou-Gabal, Hanaa
Abstract: Corona treatment of Eosin Y‐contaminated water by using a dielectric material that covers the ground electrode to avoid spark discharge (causing erosion), reduce charge leakage, and improve the electric field (as stored electrons and charges) was investigated. Elimination of the organic pollutant by gas‐phase discharge above the liquid surface in a point‐to‐plate configuration with multiple needle electrodes was studied. Eosin Y was chosen as model contaminant because of its toxicity and structure that is hard to degrade. Variables such as solution conductivity, dye concentration, pH, air gap, number of needles, and electrode materials were considered. The degree of removal increases with increasing acidity, decreasing concentration, and increasing number of pins. Abstract : Wastewater contaminated with Eosin Y dye is an environmental threat due to its toxicity, mutagenicity, and difficult degradation. Degradation of Eosin Y in water by treatment with a dielectric barrier discharge plasma was studied in a multineedle point‐to‐plate mode. The effects of solution conductivity, dye concentration, pH, air gap, number of needles, and electrode materials were investigated.